Scratching the Surface: Detecting the Presence of Viral Pathogens in Pediatric Primary Care Clinics. (4th October 2017) - Odeniyi, Folasade; Santos, Jasmine; Hanley, Samantha; Faerber, Jennifer; Localio, Russell; Metlay, Joshua; Coffin, Susan; Feemster, Kristen
Abstract: Background: Previous studies have shown that there is an increased risk of influenza-like illness (ILI) after a well visit in pediatric clinics. Despite advances in techniques to identify viruses on environmental surfaces, few studies have explored respiratory virus burden on surfaces in clinic waiting or examination rooms. We piloted an environmental surface sampling strategy to detect the presence of respiratory viruses in pediatric primary care clinics. Methods: We sampled pre-determined surfaces at two clinics (one with a mixed waiting room (MWR) and one with a separate well (WWR) and sick (SWR) waiting room from a large pediatric outpatient network in the morning and evening of one day in March 2017. Sampled surfaces included: six waiting room surfaces (door knob, adult chair handle, child chair handle, child table, toy station, reception desk, and book/magazine) and three exam room (EXR) surfaces (book/magazine, adult chair, examination table). To assess surface dirtiness, we measured adenosine triphosphate (ATP) levels with a validated assay and compared relative light units (RLUs) between morning and evening samples. To determine the presence of virus, we collected swabs from each surface which we placed in viral transport media then tested for 12 common respiratory viruses using RT-PCR. Results: We collected 96 samples (48 ATP, and 48 viral swabs). Controlling for type of clinic room (MWR, WWR, SWR, EXR), the mean evening RLU across surface types was higher (dirtier) in the evening than in the morning (evening: 1394.6 95% CI: 879.2, 1919.9; morning: 525.3 95% CI: 9.9, 1040.6). Based on threshold of >250 RLUs, 91.6% MWR, 66.6% WWR, 83.3% SWR, 58.3% EXR surface samples were considered dirty. Only 5 of the 24 surface types were found to have any virus present: rhinovirus, influenza A, metapneumovirus, and parainfluenza 3. Conclusion: Respiratory viruses were successfully isolated, but from few surfaces, possibly due to limited sample size. Notably, virus positive samples were from surfaces that children were likely to touch and ATP levels significantly increased throughout the day across all surfaces. Results suggest that environmental surfaces could be a reservoir for respiratory virus transmission in pediatric clinics and may need to be included in healthcare-associated ILI surveillance activities. Further study is needed to confirm results. Disclosures: All authors: No reported disclosures.